2008
DOI: 10.1097/ccm.0b013e31817d213d
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of right ventricular involvement in patients with acute myocardial infarction: Meta-analysis

Abstract: Our results support the view that early recognition of RVI, namely by means of right electrocardiographic leads in acute myocardial infarction, may have prognostic value. Whether or not this recognition will permit improvement of outcomes through more aggressive percutaneous coronary intervention would need to be tested in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 29 publications
0
51
0
9
Order By: Relevance
“…99 Additional published clinical, imaging, and hemodynamic variables associated with in-hospital mortality in the CS population include anoxic brain damage, end-organ hypoperfusion, elevated lactate, prior CABG, ACS pathogenesis, LV ejection fraction, RV function, pulmonary artery pulsatility index (defined as the ratio of pulmonary artery pulse pressure to right atrial pressure), mitral regurgitation, LV stroke work, cardiac power output, SBP, number of vasopressors, systemic inflammatory response syndrome, and TIMI (Thrombolysis in Myocardial Infarction) flow. 39,48,[100][101][102][103][104][105] Limitations of available models included the lack of a CS-specific derivation population, external validation, dynamic application (ie, single point in time only), applicability to all CS types, and capture of all potentially prognostic clinical, laboratory, hemodynamic, imaging, and biomarker data.…”
Section: Prognostic Models and Variablesmentioning
confidence: 99%
“…99 Additional published clinical, imaging, and hemodynamic variables associated with in-hospital mortality in the CS population include anoxic brain damage, end-organ hypoperfusion, elevated lactate, prior CABG, ACS pathogenesis, LV ejection fraction, RV function, pulmonary artery pulsatility index (defined as the ratio of pulmonary artery pulse pressure to right atrial pressure), mitral regurgitation, LV stroke work, cardiac power output, SBP, number of vasopressors, systemic inflammatory response syndrome, and TIMI (Thrombolysis in Myocardial Infarction) flow. 39,48,[100][101][102][103][104][105] Limitations of available models included the lack of a CS-specific derivation population, external validation, dynamic application (ie, single point in time only), applicability to all CS types, and capture of all potentially prognostic clinical, laboratory, hemodynamic, imaging, and biomarker data.…”
Section: Prognostic Models and Variablesmentioning
confidence: 99%
“…В мета-анализе 22 ис-следований с участием в общей сложности 7136 па-циентов с ИМ ЛЖ наличие ИМ ПЖ привело к увеличе-нию в 2,6 раза риска летальности, а также сопровож-далось высоким уровнем атрио-вентрикулярных бло-кад и желудочковых аритмий, кардиогенного шока [23,24]. Хотя прогноз при ИМ ПЖ более благоприятен, чем при ИМ ЛЖ, однако ранняя диагностика ИМ ПЖ име-ет первостепенное значение в плане выбора специфи-ческой терапии [25]. …”
Section: Discussionunclassified
“…Сочетание ИМ ПЖ с ИМ нижней стенки ЛЖ увеличивает летальность в 2,6 раза -с 6,3% (при изолированном ИМ нижней стенки ЛЖ) до 17% (при сочетанном ИМ) [1,2]. Дан-ный факт объясняется высокой частотой развития кар-диогенного шока [3]. Летальность от кардиогенного шока при ИМ ПЖ достигает 60% [4].…”
unclassified
“…Hamon et al [9] demonstrated RV dysfunction as a predictor of an adverse prognosis in STEMI without cardiogenic shock, in a meta-analysis of data from 22 studies. On the other hand, RV dysfunction in NSTE-ACS has not been widely investigated yet.…”
Section: Discussionmentioning
confidence: 99%